Simultaneous Optimization of Mismatched Filters and Controlled Amplitude Signals for Long-Range MIMO Radars - Bezoušek, Pavel; Karamazov, Simeon (IEEE (Institute of Electrical and Electronics Engineers), 2022)
This study presents a new signal and filter design procedure for long-range multiple-input multiple-output (MIMO) radars with a pulse length shorter than the return time of signals reflected by the most distant targets. The proposed algorithm adopts and radically improves the method of alternating the optimization of filters and signals, which was recently published by the same authors. It introduces full control of the signal envelope variation during the pulse, preserving acceptable peak-to-average power ratio (PAR) and signal-to-noise ratio (SNR) loss values. This state-of-the-art method allows calculation simplicity and is important for high-speed computations in adaptive applications. A gradient algorithm was used for the signal amplitude and phase optimization. The signal amplitude was controlled using a special signal construction consisting of two complex exponentials.
Současná optimalizace nepřizpůsobených filtrů a signálů s kontrolovatelnými amplitudami pro MIMO radary dlouhého dosahu
Keywords: optimization; filtering algorithms; radar; matched filters; MIMO radar; signal to noise ratio; Iterative methods; quadratic programming; noise measurement; Crosstalk; Doppler effect; iterative optimization; gradient algorithm; MIMO radar